Desenvolvimento de mudas de Moringa Oleifera Lam. em diferentes substratos - FEHLAUER, Bruna Stefanny Baroni (2019)
Moringa oleifera Lam. It has attracted the interest of numerous people due to the nutritional and medicinal benefits that the species offers. The objective of this work was to evaluate seed germination and the development of Moringa oleifera Lam. Seedlings in different substrates. The materials used to compose the substrates were: Bw Horizon of a Red Latosol; sand washed; crushed acai kernel; semidecomposed, crushed and dried cocoa shell and dry and crushed tanned bovine manure. 24 substrate compositions were tested, with nine replicates each in a completely randomized design. The experiment was evaluated after 28 days of sowing and the analyzed variables were: total height of the seedling, collection diameter and germination. For the height variable the treatments T18, T17 and T24 presented, respectively, the best means. For T24 collection, T11, T17 and T20 presented the best results and percentage of germination, T4, T6, T12, T14, T18 and T24 were the most significant. The treatment that presented the best combined result among the analyzed variables was T24. and the use of semi-decomposed cocoa residue is not recommended for the production seedlings of Moringa oleifera Lam. under the conditions of this study.